Wolf-Hirschhorn (4p-) syndrome: Prenatal diagnosis, molecular cytogenetic characterization and association with a 1.2-Mb microduplication at 8p22-p21.3 and a 1.1-Mb microduplication at 10p15.3 in a fetus with an apparently pure 4p deletion - Chih-Ping Chen; Yi-Ning Su; Yi-Yung Chen; Jun-Wei Su; Schu-Rern Chern; Yu-Ting Chen; Wen-Lin Chen; Li-Feng Chen; Wayseen Wang (Elsevier, 2011)
Objective: To present prenatal diagnosis and molecular cytogenetic characterization of Wolf-Hirschhorn syndrome (WHS) associated with microduplications at 8p and 10p in a fetus with an apparently pure 4p deletion. Case Report: A 35-year-old gravida 2, para 1 woman underwent amniocentesis at 18 weeks of gestation because of advanced maternal age. Her husband was 38 years of age. There was no family history of congenital malformations. Amniocentesis revealed a karyotype of 46,XY,del(4p16.1). The parental karyotypes were normal. Array comparative genomic hybridization (aCGH) analysis revealed a 6.5-Mb deletion at 4p16.3-p16.1, a 1.2-Mb microduplication at 8p22-p21.3, and a 1.1-Mb microduplication at 10p15.3, or arr cgh 4p16.3p16.1 (0-6,531,998 bp)×1, 8p22p21.3 (18,705,388-19,940,445 bp)×3, 10p15.3 (0-1,105,065 bp)×3. Polymorphic DNA marker analysis confirmed a paternal origin of 4p deletion. Prenatal ultrasound revealed facial dysmorphism and hypospadias. The aCGH analysis of the parents revealed no genomic imbalance. Fluorescence in situ hybridization study showed an unbalanced reciprocal translocation between chromosomes 4 and 10 at bands 4p16.1 and 10p15.3. The cytogenetic result, thus, was 46,XY,der(4)t(4;10)(p16.1;p15.3),dup(8)(p21.3p22). The parents elected to terminate the pregnancy, and a 470-g malformed fetus was delivered. Conclusion: The present case provides evidence that an apparently pure 4p deletion can be associated with subtle chromosome imbalances in other chromosomes.